(untitled) (Global Journal of Human-Social Science, 2024)
This article addresses the legal problem of femicide violence in the context of the legal regime of El Salvador (Centro América) mainly in the field of procedural law, in which women suffer due to the lack of a legal figure or a protocol for action in cases of femicide. Which establishes an analysis methodology that incorporates the gender perspective as an interpretive criterion. It is a socio-legal investigation, with an interdisciplinary approach that links the science of law with gender studies. It presents a socio-legal problem about the fundamental rights of women in the course and resolution of judicial processes. The author presents a position, based on theoretical studies, jurisprudence, and comparative law, on the need to develop criteria for judicial action with a gender perspective, aimed at the justice administration sector. To support positions in the work, the reality of El Salvador is analyzed, but experiences from other legal contexts such as Mexico, Cuba, Chile, Argentina, Guatemala, and Nicaragua are also taken up.